Primary hyperparathyroidism as first manifestation in multiple endocrine neoplasia type 2A: an international multicenter study. Issue 6 (June 2020) - Larsen, Louise Vølund; Mirebeau-Prunier, Delphine; Imai, Tsuneo; Alvarez-Escola, Cristina; Hasse-Lazar, Kornelia; Censi, Simona; Castroneves, Luciana A; Sakurai, Akihiro; Kihara, Minoru; Horiuchi, Kiyomi; Barbu, Véronique Dorine; Borson-Chazot, Francoise; et al.
Abstract : Objective: Multiple endocrine neoplasia type 2A (MEN 2A) is a rare syndrome caused by RET germline mutations and has been associated with primary hyperparathyroidism (PHPT) in up to 30% of cases. Recommendations on RET screening in patients with apparently sporadic PHPT are unclear. We aimed to estimate the prevalence of cases presenting with PHPT as first manifestation among MEN 2A index cases and to characterize the former cases. Design and methods: An international retrospective multicenter study of 1085 MEN 2A index cases. Experts from MEN 2 centers all over the world were invited to participate. A total of 19 centers in 17 different countries provided registry data of index cases followed from 1974 to 2017. Results: Ten cases presented with PHPT as their first manifestation of MEN 2A, yielding a prevalence of 0.9% (95% CI: 0.4–1.6). 9/10 cases were diagnosed with medullary thyroid carcinoma (MTC) in relation to parathyroid surgery and 1/10 was diagnosed 15 years after parathyroid surgery. 7/9 cases with full TNM data were node-positive at MTC diagnosis. Conclusions: Our data suggest that the prevalence of MEN 2A index cases that present with PHPT as their first manifestation is very low. The majority of index cases presenting with PHPT as first manifestation have synchronous MTC and are often node-positive. Thus, our observations suggest that not performing RET mutation analysis in patients with apparently sporadic PHPT would result in an extremely low false-negative rate, if no other MEN 2A component, specifically MTC, are found during work-up or resection of PHPT.